Answer:
4(x -
)² = 0
Step-by-step explanation:
Given
4x² - 4x + 1 = 0
To complete the square the coefficient of the x² term must be 1
Factor out 4 from 4x² - 4x
= 4(x² - x) + 1 = 0
add/subtract ( half the coefficient of the x- term )² to x² - x
4(x² + 2(-
)x +
-
) + 1 = 0
4(x -
)² - 1 + 1 = 0
4(x -
)² = 0
Answer:
![41.09 {cm}^{2}](https://tex.z-dn.net/?f=41.09%20%7Bcm%7D%5E%7B2%7D%20)
<em>hope</em><em> </em><em>th</em><em>i</em><em>s</em><em> </em><em>helps</em>
<em>brainliest</em><em> </em><em>appreciated</em>
<em>good</em><em> </em><em>luck</em><em>!</em><em> </em><em>have</em><em> </em><em>a</em><em> </em><em>nice</em><em> </em><em>day</em><em>!</em>
Answer:
The coefficient is 3, the number right before the variable.
Answer:
(x+7) times (x+3)
Step-by-step explanation:
Because a area of a rectangle is lw and you combine x and 3 to make x+3 and 7 and x to make x+7 and you multiply them together.
This can be solved by Newton's binomial formula
Tk+1 = (n k) a∧(n-k) b∧k k+1=7 => k=6, n=11 , a=-3x and b=-2y
T7= (11 6) (-3x)∧(11-6) (-2y)∧6 = (11*10*9*8*7)/(1*2*3*4*5) (-3x)∧5 (-2y)∧6
T7= 462 (-3x)∧5 (-2y)∧6
The correct answer is A.
Good luck!!!